Pengelolaan Dana Bantuan Operasional Sekolah Di Sekolah Dasar Negeri - Taufik Nurrochman; Farid Muhammad; Harsono Harsono; Suyatmini Suyatmini (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
. This study aims to describe the management of Regular School Operational Assistance (BOS) funds at SD Negeri 2 Sawahan, Boyolali Regency, starting from planning, implementation and accountability as well as reporting on the use of regular BOS funds by School Management. This research uses a descriptive qualitative approach, the source of this research is the school principal and BOS treasurer. Data collection uses direct interview techniques, field observations, and documenting the results. Data were analyzed using several stages starting from collecting data, sorting data by reduction, presenting data, and verifying the correctness of data. The results of data analysis concluded that the management of Regular School Operational Assistance (BOS) funds at SD Negeri 2 Sawahan had been carried out in accordance with the Technical Guidelines for the Use and Accountability of School Operational Assistance Funds for Elementary Schools in 2022, but in practice there were still obstacles such as delays in the distribution of BOS funds , discrepancies and lack of coordination in reporting BOS funds that must be corrected immediately.